Evaluating the need for coal in Kenya's electricity generation mix - Odera, Sarah (Strathmore University, 2019)
In this paper, we will compare three government-led electricity generation capacity expansion plans for Kenya, highlighting the ramifications of assumptions made in the energy planning processes to energy planning conclusions and strategy. Energy planning in Kenya has been strongly influenced by the need for economic development in the country as proposed by the Vision 2030, which aims to transform Kenya into an upper middle-income economy. This has led to proposals for nuclear and coal power in the country’s Least-Cost Power Development Plans. However, another capacity expansion plan developed by a consultant on behalf of the government decries the decision to build nuclear power and states that the decision to utilise coal should also be re-examined. We therefore compare the methodology and assumptions in these three plans with the aim of determining whether nuclear and coal power are necessary for Kenya’s electricity generation mix. Such comparison is timely and useful for regional policy-makers as it precipitates a multi-faceted picture of the key underlying challenges affecting the Kenyan electricity sector. Our comparative analysis strongly suggests updating demand forecast methods. Finally, the economic viability of coal and nuclear power do not suggest inclusion in Kenya’s expanded electricity generation mix.
Reserach Brown Bag Presentations
Keywords: Energy; Coal Mining; Electricity Generation